IMPLEMENTASI PROGRAM KOKURIKULER PERTANIAN DALAM PENCAPAIAN KETERAMPILAN DAN KEMANDIRIAN WARGA BELAJAR KESETARAAN PAKET B DI PKBM ANUGRAH BANGSA - Lufi Nurul Shofiana; Tri Joko Raharjo (STKIP Pesisir Selatan, 2026)
This study aims to analyze how agricultural co-curricular is implemented in the Package B Equality Program at PKBM Anugrah Bangsa and to identify the factors that affect its success in non-formal education. Methodology: In this study, the approach used is qualitative descriptive. Data collection was carried out through observation, in-depth interviews, and documentation Penelitianes. The informants of this study include PKBM managers, tutors, and participants of Package B. Data analysis was carried out by following the steps of data reduction, data presentation, and conclusion drawing systematically to gain a comprehensive understanding of the program implementation process. Findings: The results of the study show that the implementation of agricultural co-curricular is carried out in an adaptive and participatory manner which includes the stages of planning, direct practice, and evaluation based on learning experience. The success of the program is influenced by a clear sense of objectives, the commitment of the implementer, good communication, and the relevance of the activity to the needs of the participants. Despite limitations in facilities and land, the program continues to run well through the use of local resource strategies. Novelty: This research lies in the affirmation that the success of agricultural co-curriculars is determined by the quality of implementation, not the completeness of the facilities.